Analisis Implementasi Model Pembelajaran Berbasis Bilingual Di Madrasah Tsanawiyah Negeri Malang - Nurin Yusrina Prasetyani; Agus Tinus (Jurnal Kebijakan dan Pengembangan Pendidikan, 2017)
Abstract: This research aims to find out (1) What are the programs in implementing bilingual learning in MTsN 1 Malang? (2) What is the bilingual implementation process in MTsN 1 Malang (3) What factors are supporting and hindering the implementation? This research used a descriptive qualitative approach. Data collection techniques carried out by interview, documentation, and observation. The informants are the School Principal, Curriculum Team, and Bilingual Teachers who are used as primary and secondary data. Data analysis techniques include data reduction, data presentation, drawing conclusions and testing the validity of the data using source triangulation techniques. Location of research in MTsN 1 Malang. The results of the research showed that (1) Bilingual learning is based on the K-13 curriculum with the learning process using two languages, (2) Application of bilingual is focused on science and mathematics, (3) There is high student motivation, infrastructure facilities that support learning, and language acquisition high. There are inhibiting factors of less competent teaching staff and differences in student characteristics.Keywords: Learning Model, Bilingual, Implementation Abstrak: Peneitian ini bertujuan untuk mengetahui (1) Apa saja program dalam implementasi pembelajaran bilingual di MTsN 1 Malang? (2) Bagaimana proses implementasi bilingual di MTsN 1 Malang; (3) Faktor Apa saja yang menjadi pendukung dan penghambat dalam pelaksanaannya? Penelitian ini menggunakan pendekatan kualitatif deskriptif. Teknik pengumpulan data dilakukan dengan wawancara, dokumentasi, dan observasi. Informannya Kepala Sekolah, Tim Kurikulum, dan Guru Bilingual yang dijadikansebagai data primer dan sekunder. Teknik analisis data meliputi, reduksi data, penyajian data, penarikan kesimpulan serta pengujian keabsahan data dengan menggunakan teknik triangulasi sumber. Lokasipenelitian di MTsN 1 Kota Malang. Dari hasil penelitian menunjukkan bahwa (1) Pembelajaran bilingual dilakukan berlandaskan Kurikulum K-13 dengan proses pembelajaranya menggunakan dua bahasa, (2) Penerapan bilingual terfokus pada sains dan matematika, (3) Adanya motivasi siswa yang tinggi, sarana prasarana yang mendukung pembelajaran, dan penguasaan bahasa yang tinggi. Adanya faktor penghambat dari tenaga pengajar yang kurang kompeten dan perbedaan karakteristik siswa.Kata kunci: Model Pembelajaran, Bilingual, Implementasi